Pironetin Binds Covalently to αCys316 and Perturbs a Major Loop and Helix of α-Tubulin to Inhibit Microtubule Formation. Issue 15 (31st July 2016) - Prota, Andrea E.; Setter, Jocelyn; Waight, Andrew B.; Bargsten, Katja; Murga, Juan; Diaz, José Fernando; Steinmetz, Michel O.
Abstract: Microtubule-targeting agents are among the most powerful drugs used in chemotherapy to treat cancer patients. Pironetin is a natural product that displays promising anticancer properties by binding to and potently inhibiting tubulin assembly into microtubules; however, its molecular mechanism of action remained obscure. Here, we solved the crystal structure of the tubulin–pironetin complex and found that the compound covalently binds to Cys316 of α-tubulin. The structure further revealed that pironetin perturbs the T7 loop and helix H8 of α-tubulin. Since both these elements are essential for establishing longitudinal tubulin contacts in microtubules, this result explains how pironetin inhibits the formation of microtubules. Together, our data define the molecular details of the pironetin binding site on α-tubulin and thus offer a promising basis for the rational design of pironetin variants with improved activity profiles. They further extend our knowledge on strategies evolved by natural products to target and perturb the microtubule cytoskeleton. Graphical Abstract: Highlights: Pironetin binds covalently to Cys316 of α-tubulin. Pironetin binding perturbs the T7 loop and helix H8 of α-tubulin. Data explain how pironetin inhibits the formation of microtubules. Data extend our knowledge on mechanisms used by natural products to perturb microtubules.